The Impact Of Social Infrastructure On Economic Growth In East Java Province - Siska Wulandari (Jurnal Ekonomi dan Bisnis Airlangga, 2021)
Introduction: The process of economic development emphasizes economic growth, in which the results at a certain time will provide an overview of economic activity and increase the level of welfare of the population. This study aims to determine how much impact of Expenditures for Elementary Schools, Expenditures for Junior High Schools, Expenditures for Basic Health Services, and Expenditures for Referrals on Economic Growth in East Java Province.Methods: . The method used in this research is panel data regression analysis with Fixed Effect Model (FEM) approach.Results: Based on the results of the study, it shows that Expenditure for Elementary School , Expenditure for Junior High School , Expenditure for Basic Health Services have positive and significant impact on Economic Growth, meanwhile Expenditure for Referrals Services has a positive and insignificant impact on Economic Growth of East Java Province.Conclusion and suggestion: The local government is expected to increase economic growth in East Java Province by paying more attention to human development. Policies related to improvement in the field of education are needed by optimizing government spending to build supporting facilities for education that can support improving the quality of education. Other policies related to the health sector can be done by improving facilities and infrastructure in the health sector. This is because there are still remote areas that have limited facilities and inadequate infrastructure.